Health impact (HI-FMEA) decision support application for hospital health technology management - David Mutia; Peter Muchiri; Michael Munywoki; James Wakiru (International Journal of Research in Industrial Engineering)
The research aims to create an innovative Healthcare Impact Failure Mode and Effects Analysis (Hi-FMEA) framework approach that integrates patient safety in identifying and prioritizing critical failure modes in medical equipment and derive appropriate mitigation strategies for the identified critical failure modes. The developed Hi-FMEA is a robust framework for identifying, evaluating, and prioritizing failure modes of critical medical equipment, in this case, dialysis machines. Incorporating patient safety, a clear novelty of the technique, enables biomedical engineers to identify and rank critical failure modes. The Hi-FMEA framework was established through risk assessment and patient safety analysis. It involved several factors that govern patient safety and risk: frequency of failures, patient delay time, maintainability, and redundancy. To validate this framework, data was collected in a case study public hospital, pre-processed, and failure modes identified through various data exploratory techniques. Appropriate maintenance strategies to mitigate the critical failure modes were systematically selected using a modified decision tree. Based on the Hi-FMEA technique, leakages and flow pump failure were identified as critical failure modes, and a modified decision tree recommended Condition Based Maintenance (CBM) and design out maintenance strategies for the critical failure modes. The developed framework incorporating Hi-FMEA and decision tree identifies critical failure modes and respective maintenance mitigation strategies, ultimately improving patient safety and ensuring strategic resource allocation.